Sestrin2, as a negative feedback regulator of mTOR, provides neuroprotection by activation AMPK phosphorylation in neonatal hypoxic-ischemic encephalopathy in rat pups - Shi, Xudan (J Cereb Blood Flow Metab, 2016)
Hypoxic-ischemic encephalopathy is a condition caused by reduced oxygen and cerebral blood flow to the brain resulting in neurological impairments. Effective therapeutic treatments to ameliorate these disabilities are still lacking. We sought to investigate the role of sestrin2, a highly conserved stress-inducible protein, in a neonatal rat hypoxic-ischemic encephalopathy model. Ten-day-old rat pups underwent right common carotid artery ligation followed by 2.5 h hypoxia. At 1 h post hypoxic-ischemic encephalopathy, rats were intranasally administered with recombinant human sestrin2 and sacrificed for brain infarct area measurement, Fluoro-Jade C, immunofluorescence staining, Western blot, and neurological function testing. rh-sestrin2 reduced brain infarct area, brain atrophy, apoptosis, ventricular area enlargement, and improved neurological function. Western blot showed that sestrin2 expression levels were increased after treatment with rh-sestrin2, and sestrin2 exerts neuroprotective effects via activation of the adenosine monophosphate-activated protein kinase pathway which in turn inhibits mammalian target of rapamycin signaling resulting in the attenuation of apoptosis. In conclusions: Sestrin2 plays an important neuroprotective role after hypoxic-ischemic encephalopathy via adenosine monophosphate-activated protein kinase signaling pathway and serves as a negative feedback regulator of mammalian target of rapamycin. Administration of rh-sestrin2 not only reduced infarct area and brain atrophy, but also significantly improved neurological function.